2021
DOI: 10.1111/jbg.12642
|View full text |Cite
|
Sign up to set email alerts
|

Across‐country genomic predictions in Norwegian and New Zealand Composite sheep populations with similar development history

Abstract: The goal of this study was to assess the feasibility of across‐country genomic predictions in Norwegian White Sheep (NWS) and New Zealand Composite (NZC) sheep populations with similar development history. Different training populations were evaluated (i.e., including only NWS or NZC, or combining both populations). Predictions were performed using the actual phenotypes (normalized) and the single‐step GBLUP via Bayesian inference. Genotyped NWS animals born in 2016 (N = 267) were used to assess the accuracy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Prediction bias, as a property of the method and the population under evaluation, is the expectation of the difference between average true and predicted breeding value; bias is zero under ideal conditions and can be approximated by the difference between the average (G)EBV in the whole and partial data sets (Legarra & Reverter, 2018 ). The observation that GEBV and EBV for most of the scenarios across traits were over‐estimated in the Rambouillet sheep was consistent with other studies (Brown et al, 2018 ; Moghaddar et al, 2019 ; Oliveira et al, 2021 ). Our conclusions regarding the benefit of including genomic information in prediction based on dispersion followed the same pattern observed for the GEBV prediction accuracies; this was likely because they are affected by similar factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Prediction bias, as a property of the method and the population under evaluation, is the expectation of the difference between average true and predicted breeding value; bias is zero under ideal conditions and can be approximated by the difference between the average (G)EBV in the whole and partial data sets (Legarra & Reverter, 2018 ). The observation that GEBV and EBV for most of the scenarios across traits were over‐estimated in the Rambouillet sheep was consistent with other studies (Brown et al, 2018 ; Moghaddar et al, 2019 ; Oliveira et al, 2021 ). Our conclusions regarding the benefit of including genomic information in prediction based on dispersion followed the same pattern observed for the GEBV prediction accuracies; this was likely because they are affected by similar factors.…”
Section: Discussionsupporting
confidence: 90%
“…The genomic prediction accuracies observed in our study were within the range for most of the economic traits in sheep, which is between 0.20 and 0.50 according to Brown et al (2018), especially when using α of 0.95 to construct the G matrix. Oliveira et al (2021) observed prediction accuracies for BWT ranging from 0.06 to 0.13 using H‐BLUP for Norwegian White and New Zealand Composite sheep populations. Unlike what was observed in the current study, Moghaddar et al (2019) showed accuracies for genomic predictions ranging between 0.40 to 0.60 for PWT, 0.30 to 0.40 for yearling clean fleece weight, and 0.30 to 0.50 for YFD using BayesR and GBLUP for purebred Merino and crosses between Merino and Border Leicester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference populations and pipelines for analysis has already been well established for these breeding programmes (Brown et al, 2018; Swan et al, 2014), but across country genomic prediction (e.g. de Oliveira et al, 2021) is yet to be investigated for Merino sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, combining data from several populations is only feasible if they are genetically related (Lund et al, 2014;Rezende et al, 2020). However, recent studies in Norwegian and New Zealand sheep with similar development history, but reduced recent exchange of genetic material, have reported that collaborative genomic analyses could still be feasible (Oliveira et al, 2020;Oliveira et al, 2022).…”
Section: Introductionmentioning
confidence: 99%